Evolutionary biology: an essential basic science for the training of the next generation of psychiatrists. (December 2019) - Abed, Riadh; Ayton, Agnes; St John-Smith, Paul; Swanepoel, Annie; Tracy, Derek K.
Summary: Evolutionary science can serve as the high-level organising principle for understanding psychiatry. Evolutionary concepts generate new models and ideas for future psychiatric study, research, policy and therapy. The authors accordingly make the case for the inclusion of evolutionary biology in the postgraduate education of psychiatric trainees.